Clinical decision making is improved by BioFire Pneumonia Plus in suspected lower respiratory tract infection after lung transplantation: Results of the prospective DBATE‐IT study. Issue 1 (6th October 2021) - Kayser, Moritz Z.; Seeliger, Benjamin; Valtin, Christina; Fuge, Jan; Ziesing, Stefan; Welte, Tobias; Pletz, Mathias W.; Chhatwal, Patrick; Gottlieb, Jens
Abstract: Background: Lower respiratory tract infections (LRTIs) are a significant cause of morbidity and mortality in lung transplant (LTx) recipients. Timely and precise pathogen detection is vital to successful treatment. Multiplex PCR kits with short turnover times like the BioFire Pneumonia Plus (BFPPp) (manufactured by bioMérieux) may be a valuable addition to conventional tests. Methods: We performed a prospective observational cohort study in 60 LTx recipients with suspected LRTI. All patients received BFPPp testing of bronchoalveolar lavage fluid in addition to conventional tests including microbiological cultures and conventional diagnostics for respiratory viruses. Primary outcome was time‐to‐test‐result; secondary outcomes included time‐to‐clinical‐decision and BFPPp test accuracy compared to conventional tests. Results: BFPPp provided results faster than conventional tests (2.3 h [2–2.8] vs. 23.4 h [21–62], p < 0.001), allowing for faster clinical decisions (2.8 [2.2–44] vs. virology 28.1 h [23.1–70.6] and microbiology 32.6 h [4.6–70.9], both p < 0.001). Based on all available diagnostic modalities, 26 (43%) patients were diagnosed with viral LRTI, nine (15 %) with non‐viral LRTI, and five (8 %) with combined viral and non‐viral LRTI. These diagnoses were established by BFPPp in 92%, 78%, and 100%, respectively. The remaining 20 patients (33 %) received a diagnosis other than LRTI. Preliminary therapies based on BFPPp results were upheld in 90% of cases. There were six treatment modifications based on pathogen‐isolation by conventional testing missed by BFPPp, including three due to fungal pathogens not covered by the BFPPp. Conclusion: BFPPp offered faster test results compared to conventional tests with good concordance. The absence of fungal pathogens from the panel is a potential weakness in a severely immunosuppressed population.